Politik Hukum Partai Politik dan Pemilihan Umum - Muhtadin, Muhtadin (Lembaga Yasin AlSys, 2023)
According to modern democracies, political parties and elections are institutions that cannot be separated from one another. Each Political Party will always try to gain great popular support during the General Election so that the People's Representative Institution is dominated by the Political Party concerned. General elections are people's parties which are a manifestation of the principle of people's sovereignty, so it is during elections that the people are given freedom in making political choices and attitudes through candidates for people's representatives who are members of Political Parties. The will of the people is the basis of government power. That will be born in periodic and honest elections conducted in general elections and in common with secret voting, by means of free and equal voting. Thus, freedom, honesty, secrecy and equality are essential in the administration of elections. Political, legal, political party and electoral policies in guarding democratization in Indonesia have undergone significant shifts over time. General elections are considered a real form of democracy and the most concrete form of public participation in participating in the administration of the state.